Acknowledgement System in Introduction Section of Engineering Research Articles - Mulyati Khorina; Saudin Saudin; Mohammad Febryanto (Linguistics and ELT Journal, 2021)
Citing other authors works is essential in Research Articles (RAs). The citation is used to support claims academically. The citation is described as a way to interact with the readers and to acknowledge other scholars. Viewing from Appraisal framework developed by Martin and White [1] which is based on Halliday’s interpersonal metafunction, this activity is described as Engagement system. This study focused on exploring acknowledgement, a branch of Engagement system, found in Mechanical Engineering RAs published by Elsevier. Applying qualitative method, the data were taken from five research articles of Mechanical Engineering in 2021. Thus, the data were examined using the framework of Engagement system. What can be highlighted from the results is that the acknowledgment serving as citation may be realized by projection of mental and verbal clauses with limited choice of lexical verbs, such as report, emphasize, propose, realizing both types of process. Nevertheless, the implication of this study may help EAP practitioners in teaching citation of RAs for Mechanical Engingeering learners.